2015
DOI: 10.1021/acs.jpcc.5b06070
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Pd Multilayers on Re(0001): The Role of Charge Transfer

Abstract: Understanding the origin of the properties of metal-supported metal thin films is important for the rational design of bimetallic catalysts and other applications, but it is generally difficult to separate effects related to strain from those arising from interface interactions. Here we use density functional (DFT) theory to examine the structure and electronic behavior of fewlayer palladium films on the rhenium (0001) surface, where there is negligible interfacial strain and therefore other effects can be iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…[22a, [23][24][25] Thed irection of the CLSs appear to indicate ac harge transfer from the Pt shell to Wi nt he core,w hich would result in am ore attractive force on Pt electrons and more repulsive force on Welectrons.H owever,e xamination of the work functions suggest an et transfer in the opposite direction, indicating that asimple interatomic charge transfer is inadequate in describing the CLSs for metal overlayer systems,a schanges in the local potential around the core electrons arising from bonding and rehybridization can have astronger effect on the binding energy than an et difference in charge on the overall atom. [23][24][25] Although the exact cause is uncertain, these CLSs do demonstrate that the electronic and chemical properties of Pt are significantly altered by the presence of the TMC or TMN core and can also provide am easure of potential changes in the reactivity of Pt. Weinert and Watson showed that CLSs for metal overlayers are accompanied by similar shifts in the valence d-band center, [23] and Ontaneda et al determined an ear 1:1c orrelation for core level and d-band shifts of Pd overlayers on Re.…”
Section: Zuschriftenmentioning
confidence: 99%
“…[22a, [23][24][25] Thed irection of the CLSs appear to indicate ac harge transfer from the Pt shell to Wi nt he core,w hich would result in am ore attractive force on Pt electrons and more repulsive force on Welectrons.H owever,e xamination of the work functions suggest an et transfer in the opposite direction, indicating that asimple interatomic charge transfer is inadequate in describing the CLSs for metal overlayer systems,a schanges in the local potential around the core electrons arising from bonding and rehybridization can have astronger effect on the binding energy than an et difference in charge on the overall atom. [23][24][25] Although the exact cause is uncertain, these CLSs do demonstrate that the electronic and chemical properties of Pt are significantly altered by the presence of the TMC or TMN core and can also provide am easure of potential changes in the reactivity of Pt. Weinert and Watson showed that CLSs for metal overlayers are accompanied by similar shifts in the valence d-band center, [23] and Ontaneda et al determined an ear 1:1c orrelation for core level and d-band shifts of Pd overlayers on Re.…”
Section: Zuschriftenmentioning
confidence: 99%
“…On the contrary, a tensile strain will lead to a decrease in the d‐bandwidth if no charge transfer occurs. This results in the upshifting of the d‐band center toward the Fermi level and stronger interactions with surface adsorbates …”
Section: Introductionmentioning
confidence: 99%
“…This results in the upshifting of the d-band center toward the Fermi level and stronger interactions with surface adsorbates. [6] Strains are generally created based on the lattice mismatch effect, which can occur after depositing the desired material onto a substrate with a different lattice parameter ( Figure 1b). [7] This creates either a compressive or tensile strain localized at the interface between the desired material and the substrate.…”
mentioning
confidence: 99%
“…[23][24][25] Although the exact cause is uncertain, these CLSs do demonstrate that the electronic and chemical properties of Pt are significantly altered by the presence of the TMC or TMN core and can also provide am easure of potential changes in the reactivity of Pt. [25] Thus,t he observed lower energy core electrons (higher XPS binding energy) of Pt in these coreshell materials should translate to ad own-shifted d-band center compared to that of apure Pt surface and consequently weaker adsorbate binding energies. [25] Thus,t he observed lower energy core electrons (higher XPS binding energy) of Pt in these coreshell materials should translate to ad own-shifted d-band center compared to that of apure Pt surface and consequently weaker adsorbate binding energies.…”
Section: Communicationsmentioning
confidence: 81%
“…[22a, [23][24][25] Thed irection of the CLSs appear to indicate ac harge transfer from the Pt shell to Wi nt he core,w hich would result in am ore attractive force on Pt electrons and more repulsive force on Welectrons.H owever,e xamination of the work functions suggest an et transfer in the opposite direction, indicating that asimple interatomic charge transfer is inadequate in describing the CLSs for metal overlayer systems,a schanges in the local potential around the core electrons arising from bonding and rehybridization can have astronger effect on the binding energy than an et difference in charge on the overall atom. [22a, [23][24][25] Thed irection of the CLSs appear to indicate ac harge transfer from the Pt shell to Wi nt he core,w hich would result in am ore attractive force on Pt electrons and more repulsive force on Welectrons.H owever,e xamination of the work functions suggest an et transfer in the opposite direction, indicating that asimple interatomic charge transfer is inadequate in describing the CLSs for metal overlayer systems,a schanges in the local potential around the core electrons arising from bonding and rehybridization can have astronger effect on the binding energy than an et difference in charge on the overall atom.…”
Section: Communicationsmentioning
confidence: 99%